Offshoring: The Next Industrial Revolution? - Blinder, Alan S. (Foreign Affairs)
The United States must begin to prepare for the huge economic changes that will be brought about by offshoring. Fragmentary studies suggest that well under a million service-sector jobs in America have been lost to offshoring so far, but continuing improvements in technology and global communications almost guarantee that the future will bring a significant increase in the offshoring of “impersonal services,” services that can be delivered electronically over substantial distances with little or no degradation in quality. The United States and other industrial nations have benefited from comparable changes in the past, but in order to do so again, the governments and societies of the developed world must face up to the huge, complex, and multifaceted challenges of offshoring. America's information systems, trade policies, educational systems, social welfare programs, and politics all must adjust to new realities.